Edukasi Penguatan Identitas Kesenian Bantengan melalui Nilai-Nilai dan Karakteristik sebagai Warisan Budaya Lokal Kota Malang - Ahmad Wildan Syidad; Sulas Nuranira; Farikha Maghfiratul Hijjah; Moh Andre Fahmi Sugara; Listyo Yudha Irawan; Mey Lafaiza Sukmaning Haresa; Alifia Lafi Illiyin; Siti Haeriyah; Risma Agustia Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
Indonesia possesses a rich diversity of intangible cultural heritage that must be preserved through education to remain relevant to younger generations. One of the local cultural heritages of Malang City is the Bantengan traditional performance, which embodies historical, philosophical, character-building, and cultural identity values, yet students' understanding of these meanings remains limited. This community service program aimed to strengthen the identity of Bantengan by providing education on its values and characteristics as a form of local cultural heritage. The program employed a participatory educational approach consisting of preparation, educational sessions, interactive discussions with Bantengan practitioners, educational quizzes, and evaluation and reflection. The results showed that participants actively engaged in all activities, demonstrated a better understanding of the history, values, and characteristics of Bantengan, and developed greater awareness of the importance of preserving local culture. The discussion indicated that the involvement of cultural practitioners and interactive learning methods contributed to improving participants' understanding while supporting culture-based character development. In conclusion, local culture-based education is an effective strategy for strengthening students' cultural identity while promoting the sustainable preservation of Bantengan traditional art.